2020
DOI: 10.1080/11038128.2020.1770330
|View full text |Cite
|
Sign up to set email alerts
|

Internet opportunities and risks for adolescents with intellectual disabilities: A comparative study of parents’ perceptions

Abstract: Background: In contemporary society internet and digital competencies are used to perform activities. Aim: The aim of this study is to investigate opportunities and risks of internet use as perceived by the parents of adolescents with intellectual disabilities (ID) in comparison with a national reference group of parents of adolescents. Methods: This was a cross-sectional study with group comparisons using a national survey. Analyses were carried out using Fisher's exact test and logistic regression to control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…In developing digital competencies and rejecting risk‐averse approaches, digital inclusion will increase alongside online skills and resilience. This highlights the importance for those supporting people with learning disabilities to deepen their own digital knowledge to support positive risk taking in Internet use to enable people with learning disabilities to gain increased digital competencies (Alfredsson Ågren et al., 2020b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In developing digital competencies and rejecting risk‐averse approaches, digital inclusion will increase alongside online skills and resilience. This highlights the importance for those supporting people with learning disabilities to deepen their own digital knowledge to support positive risk taking in Internet use to enable people with learning disabilities to gain increased digital competencies (Alfredsson Ågren et al., 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent research by Alfredsson Ågren et al. (2020b) found that a higher proportion of parents of adolescents with learning disabilities perceived opportunities associated with Internet use for their adolescent than the parents of non‐disabled adolescents and a lower proportion of parents of adolescents with learning disabilities perceive negative consequences and have concerns about online risks. The conflicting views held by parents and professionals are an area that would be interesting to explore further in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include conference calls, online broadcasts, group chats on social networks and instant messaging, online tests, etc. At the technological level, the most widely applied educational systems are Google Classroom, Chamilo LMS, Microsoft Teams, Moodle, NEO LMS, Schoology, Edmodo and Blackboard Open LMS (Alfredsson et al, 2020). Within virtual platforms there should be scientific social networks to foster personal educational and disseminate scientific knowledge (Sun et al, 2020) Excessive internet use by university students can alter hormone levels due to dependence on virtual networks (Wahab, 2020).…”
Section: Distance Learningmentioning
confidence: 99%
“…In a comparative study of the internet use of young people with and without learning disabilities in Sweden, Alfredsson Ågren et al ( 2020a ) found fewer people with learning disabilities accessed the internet, with information searching the greatest difference between the two groups. The importance of support and empowerment to enable effective internet access has also been highlighted (Molin et al 2017 ; Shpigelman, 2018 ), particularly as people with learning disabilities might be at higher risk of online bullying (Alfredsson Ågren et al, 2020b ). However, people can be further excluded if too much weight is given to perceived online risks—which might lead to gatekeeping and restrictions of access—but not enough effort is put into equipping people with skills to manage this risk and learn to navigate the online world (D. Chadwick, 2019 ).…”
Section: Introductionmentioning
confidence: 99%